Youth and family involvement in the development of a plain language trial results communication tool: CommuniKIDS - Ami Baba; Dawn P. Richards; Maureen Smith; Nicole Pallone; Shelley Vanderhout; Matthew Prebeg; Ellen B. M. Elsman; Beth K. Potter; Martin Offringa; Nancy J. Butcher (Research Involvement and Engagement, 2023)
Abstract Background Pediatric trials are possible through voluntary participation of children, youth (age ≤ 18 years), and their families. Despite important arguments for trialists to provide trial progress or results, and evidence that participants desire it, this information remains rarely shared with youth and their families. Little guidance exists on how trialists can best communicate trial results back to participants and their families. Guided by Liabo et al.’s framework, we describe how we developed a pediatric-specific, “plain language summary” clinical trial results template called CommuniKIDS with an adult patient partner, family partner (parent), youth advisors, and parent advisors, taking into account their unique knowledge needs and preferences. Main text Patient and Public Involvement (PPI) was integrated in the development of the CommuniKIDS template. In collaboration with Clinical Trials Ontario, we used a generic trial results template as a starting point. The core project leadership team included a patient partner and a family partner from project inception to completion. Five youth (ages 13–18 years) and eight parent advisors were consulted at each point of the development process through three virtual workshops conducted separately; youth workshops were led by a youth facilitator. During these workshops, advisors agreed on the importance and value of sharing trial results, and expressed their preferences on content, format, and timing of sharing trial results. PPI-led improvements included the addition of three new sections to the CommuniKIDS template: “at a glance,” “side effects,” and “next steps.” We reflect on our PPI strategy in the context of five “values” and six “practicalities” identified as good PPI principles, and summarize lessons learned when collaborating with youth and families from this project. Conclusion Involvement of a patient partner, a family partner, youth advisors, and parent advisors in the development of CommuniKIDS was critical to create a clinical trial results template that is useful and relevant to its end-users. To our knowledge, CommuniKIDS is the first to meaningfully engage youth and parents as advisors and partners in developing a plain language summary results template for pediatric trial participants and their families. Our experience of co-developing CommuniKIDS demonstrates that meaningful PPI can be achieved in trial results communication and knowledge translation practices. This report provides resources for those seeking to involve youth and families in their initiatives and in meaningfully sharing trial results.